Integration as a way to strengthen the competitive advantages of corporations - E. V. Pustynnikova; V. V. Baklushinsky (Вестник университета)
The formation, functioning and development of organisations in the conditions of modern realities focuses on the search for the most constructive and effective directions of their development, contributing to the strengthening of competitive advantages. In this direction, as a rule, measures are implemented aimed at adapting to the external and internal conditions of further development. Often, the activities implemented at the micro environment level are focused on cost optimisation, and at the macro environment level, the main attention is paid to strengthening the stability of inter-corporate relations. One of the modern approaches in this direction, which is quite common in economic practice, is the integration process aimed at obtaining a synergetic effect as an additional resource that contributes to strengthening the competitiveness of corporate structures in market conditions. In turn, integration processes determine the need to develop a systematic approach to management not only in the format of a specific corporate structure, but in general, in the format of an economic system consisting of several economic entities interconnected with each other. The purpose of this study is to systematise the management processes of corporate structures that are interconnected by the conditions of mutually beneficial cooperation.